Synergistic effects of natural products in combination with anticancer agents in prostate cancer: A scoping review - Cheon, Chunhoo; Ko, Seong-Gyu (Frontiers in Pharmacology, 2022)
Background: Prostate cancer is the second most common cancer in men and has the fourth highest mortality among men worldwide. Different combination therapies for cancer are being tested, and among them, the integration of natural products is increasing. This study reviews research on the combination of anticancer drugs and natural products for the treatment of prostate cancer and suggests future directions in this field. Methods: Articles were identified by searching the PubMed, Embase, and Cochrane Library databases. Search keywords included the following: “Antineoplastic agents,” “Anticancer drug,” “Phytotherapy,” “Natural product,” “Drug synergism,” and “Synergistic effect”. The selection process focused on whether the differences in efficacy of anticancer drugs were evaluated when combined with natural products. Results: Nineteen studies were included. All 19 studies evaluated efficacy in vitro, as well as 10 in vivo. There were 13 studies on a single compound extracted from natural products, three studies on mushroom and herb extracts, and three studies on herbal medicines consisting of three herbs, and a dietary supplement containing ten herbs. Cancer cell lines used were PC-3 in nine studies, LNCaP in six studies, C4-2 in five studies, DU-145 in four studies, and 22Rv1 in two studies. Anti-cancer drugs co-administered were as follows: docetaxel in nine studies, doxorubicin and enzalutamide in three studies, paclitaxel and suberoylanilide hydroxamic acid in two studies, and cisplatin, vincristine and bicalutamide in one study each. Conclusion: Although prostate cancer is prevalent worldwide, there are relatively few studies on the use of natural products with anticancer agents as treatment. Since it has reported that the efficacy of anticancer drugs is enhanced by coadministration of natural products, it is necessary to conduct further studies on this.